The Impact of Personality Styles on Workers’ Professional Adjustment in The Light of Modern Organizations - SNANI, Loubna; BOUATTIT, Djalaleddine (Journal of Human Sciences, 2025)
The success of every organization is related to the extent of its ability to provide active human resources and achieve its goals. As the worker is a human being before being a producer characterized by independence and his love of achieving wealth, so giving priority to him before the organization is the secret of its success. Therefore, seeking to understand his desires and needs can contribute to raising his morale and the level of professional adjustment at work. Through our article, we concluded that understanding an individual’s personality contributes to achieving professional adjustment also contributes to developing his skills and improving his performance in order to achieve the organization’s future goals.